Toothbrushing and Oral Care Activities of Autistic and Non-Autistic Latino Children - Lucía I. Floríndez; Dominique H. Como; Daniella C. Floríndez; Francesca M. Floríndez; Evelyn Law; Jose C. Polido; Sharon A. Cermak (MDPI AG, 2022)
Background: Oral care activities, e.g., toothbrushing, are habitual occupations often considered routine. However, for autistic children, performing these routine dental practices can be challenging due to the child's sensory sensitivities, unique executive function, and the complicated way in which autistic children conceptualize structure and habits. Limited research exists exploring the nuances of oral care routines in the autistic population, and more knowledge is needed to support targeted education interventions to improve oral care and address health inequities. The purpose of this study was to examine videos of oral care routines in the home to understand how oral care activities, such as toothbrushing, were performed by autistic and non-autistic Latino/a children. Methods: Parents/caregivers from eighteen Latino/a families with children between 6 and 12 years old (n = 10 autistic children and n = 8 non-autistic children) video recorded their child's oral care routines for three days. The research team blindly coded and analyzed these videos using an oral care observation template to understand how these activities were uniquely performed by the children. Results: Eighty-five oral care videos were analyzed for this study. In addition to noting areas of oral care that can be improved, which included length of brushing and using the correct brushing technique, we identified two themes related to the differences between oral care practices in the autistic and non-autistic children: parent involvement and modifications. Conclusions: Qualitative findings show that parental involvement was documented especially in the case of autistic children, and that two types of modifications, habitual and sensory, were observed that demonstrated parents being aware of the needs of their autistic child and modifying the oral care activity to meet those needs. By synthesizing observations from the oral care videos into suggestions for practitioners working with families, we hope to supplement knowledge about effective oral care practices for autistic and non-autistic Latino/a children, thereby improving overall oral health and reducing oral health inequities in this population.